The First Results of the Photometric Observation of Selected Asteroids on KT-50 Telescope of Mobitel Complex of RI «MAO» - Pomazan, A.V.; Maigurova, N.V. (Science and Innovation, 2024)
The first results of the photometric observations of asteroids performed on the telescope KT-50 of Mobitel complex (SRI MAO) during 2016 are presented in the paper. Asteroids were selected based on the infrared survey NEOWISE, moving objects catalog SDSS MOC-3 and MPC database. Selected asteroids have a relatively high albedo (pV>0.2) and are located in the Outer Main Belt (semi-major axis a>0.28 a.u.). The observations were made using filter close to the Rc standard band of Cousins system. Standard deviations of the instrumental differential magnitude measurements were in the range of 0.01m-0.03m for a 10m-15.5m reference stars. The light curve based on the results of the differential aperture photometry was obtained from long series of observations of the asteroid (2144) Marietta.